2013
DOI: 10.1016/j.mmcr.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

An environmental Sporothrix as a cause of corneal ulcer

Abstract: In this case we introduce Sporothrix pallida, a non-pathogenic environmental Sporothrix species as a cause of infectious keratitis in a corneal transplant recipient. Human infections caused by S. schenckii are well-known but human infection with Sporothrix pallida has not been previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 11 publications
0
42
0
1
Order By: Relevance
“…Based on the latter study, Romeo and collaborators studied the molecular phylogeny and epidemiology of S. schenckii complex strains isolated in Italy, and demonstrated that 26 environmental strains co-clustered with S. pallida and two clinical strains grouped with S. schenckii stricto sensu [13]. Nonetheless, a recent report showed that S. pallida caused keratitis in a corneal transplant recipient [14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the latter study, Romeo and collaborators studied the molecular phylogeny and epidemiology of S. schenckii complex strains isolated in Italy, and demonstrated that 26 environmental strains co-clustered with S. pallida and two clinical strains grouped with S. schenckii stricto sensu [13]. Nonetheless, a recent report showed that S. pallida caused keratitis in a corneal transplant recipient [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Molecular studies have identified Sporothrix brasiliensis, Sporothrix globosa, Sporothrix luriei, Sporothrix mexicana, Sporothrix pallida and Sporothrix schenckii, the most common species globally, as responsible to sporotrichosis in different regions. [1][2][3][4][5][6][7][8][9] The metropolitan region of Rio de Janeiro is hyperendemic for cat-associated sporotrichosis, 10,11 primarily due to S. brasiliensis. 1,5 S. brasiliensis patients have presented with acute, chronic, fixed, lymphangitic, mucosal, disseminated and relapsing sporotrichosis, as well as manifestations of hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Sporothrix pallida was also found to be associated with the native subcortical beetle Ctonoxylon sp. 1 (Musvuugwa, 2014) and is known from many other environments including water sediments, soil, the sporophore of a slime-mould (De Meyer et al 2008) and from a corneal ulcer of a human patient (Morrison et al 2013). This fungus is, therefore, not very host and/or vector specific and may easily move from one environment to the next.…”
Section: Selection Of Study Organismsmentioning
confidence: 99%